List of birds sighted for Fall 1985 compiled by Ronald Harms - Harms, Ronaldet al (1985)
A note listing birds sighted by Ronald Harms dated November 22, 1985. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of Fall 1985. Epson - sheet feed/flatbed